Dynamic modelling of VSCs in a dq rotating frame for pole‐to‐pole dc fault study. Issue 4 (1st March 2017) - Lin, Weixing; Jovcic, Dragan
Abstract : As the future dc grids will involve numerous converter systems, the accuracy and speed of their modelling becomes of high importance. The modelling in a rotating dq frame is able to transform the quantities from ac variables to dc variables resulting in significantly improved simulation speed. dq analytical modelling is normally used only for dynamic studies with voltage source converter (VSC), while large‐disturbance dc faults are commonly studied in static abc frame. A new dq frame modelling method for VSC, including modular multilevel converter topology, for dc fault study is proposed. A unified modelling of the VSC for both dynamic and dc fault study is therefore developed. The model is separately presented for other fault‐tolerant VSC, like LCL (inductor–capacitor–inductor)‐VSC. Simulation results verified that the proposed model is accurate when compared with detailed switching model on PSCAD/EMTDC. The proposed unified VSC model is able to replace the detailed switching model for both dc fault (only pole‐to‐pole dc fault is studied) and dynamic studies. The modelling approach opens the possibility for modelling large dc grids in dq frame for wide range of operating conditions.